2022
DOI: 10.3390/jof8070663
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of ß-d-Glucan Assay for the First-Line Diagnosis of Pneumocystis Pneumonia and for Discriminating between Pneumocystis Colonization and Pneumocystis Pneumonia

Abstract: According to the immunodepression status, the diagnosis of Pneumocystis jirovecii pneumonia (PjP) may be difficult. Molecular methods appear very sensitive, but they lack specificity because Pj DNA can be detected in Pneumocystis-colonized patients. The aim of this study was to evaluate the value of a serum ß-d-Glucan (BDG) assay for the diagnosis of PjP in a large cohort of HIV-negative and HIV-positive patients, either as a first-line diagnostic test for PjP or as a tool to distinguish between colonization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
11
2
Order By: Relevance
“…In patients unable to endure a bronchoscopy, serum β-D-glucan has a high NPV that allows rule-out PJP in patients with low to moderate grade of suspicion. In fact, Bigot et al propose to do this test prior to bronchoscopy and to avoid it if test result is negative [ 245 ]. Patients with high grade of suspicion may need molecular techniques in respiratory samples.…”
Section: Resultsmentioning
confidence: 99%
“…In patients unable to endure a bronchoscopy, serum β-D-glucan has a high NPV that allows rule-out PJP in patients with low to moderate grade of suspicion. In fact, Bigot et al propose to do this test prior to bronchoscopy and to avoid it if test result is negative [ 245 ]. Patients with high grade of suspicion may need molecular techniques in respiratory samples.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted from the USA [ 50 52 , 68 , 73 ]; three studies, each were conducted in South Africa [ 67 , 72 , 90 ], Japan [ 81 , 84 , 85 ], and Thailand [ 61 , 78 , 86 ]; two studies, each were conducted in Iran [ 75 , 80 ], France [ 45 , 66 ], and Mexico [ 40 , 47 ]; one study each was conducted in Ethiopia [ 39 ], Tanzania [ 60 ], Malawi [ 57 ], Spain [ 38 ], Cameroon [ 76 ], India [ 54 ], Taiwan [ 89 ], Zambia [ 79 ], and a study was from five European countries (France, Austria, Belgium, Croatia, Germany) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our random-effects model showed that in twenty-nine eligible studies [ 38 40 , 45 , 47 , 50 52 , 54 , 57 , 60 , 61 , 66 68 , 70 , 72 , 73 , 75 , 76 , 78 81 , 84 86 , 89 , 90 ], the pooled prevalence of HAP was 35.4% (95% CI:23.8 to 47.9; I 2 : 99.4%) ( Table 2 ). There is a negligible publication bias between studies (intercept: 6.946; 95% CI:-24.750 to 38.642; P = 0.6566).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,3) β-D-glucan is a cell wall component of P jirovecii and has been found to have a heightened sensitivity to diagnose PJP and can be used as an initial screening method. 19 Retrospective studies did not find it a valuable prognostic factor for diagnosis or respiratory burden. 20,21 However, it correlated with bronchoalveolar lavage fungal load in earlier studies.…”
Section: Discussionmentioning
confidence: 98%